2013
DOI: 10.1111/aogs.12296
|View full text |Cite
|
Sign up to set email alerts
|

The cervical mucus plug inhibits, but does not block, the passage of ascending bacteria from the vagina during pregnancy

Abstract: Objective To evaluate the microbial load and the inflammatory response in the distal and proximal parts of the cervical mucus plug. Design Experimental research. Population Twenty women with a normal, singleton pregnancy. Sample Vaginal swabs and specimens from the distal and proximal parts of the cervical mucus plug. Methods. Immunohistochemistry, enzyme-linked immunosorbent assay, quantitative polymerase chain reaction and histology. Results The total bacterial load (16S rDNA) was significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 27 publications
0
54
0
6
Order By: Relevance
“…Patients with a CL 15 mm had a higher rate of positive AF culture [26% (15/57)] than patients with a CL !15 mm [3.8% (13/344)] [220]. It is unclear if a short cervix leads to compromised innate immunity following the loss of the anti-microbial properties of the cervical mucus plug [224][225][226][227][228][229] and predisposes to ascending intra-amniotic infection, or alternatively, if intra-amniotic infection leads to a short cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a CL 15 mm had a higher rate of positive AF culture [26% (15/57)] than patients with a CL !15 mm [3.8% (13/344)] [220]. It is unclear if a short cervix leads to compromised innate immunity following the loss of the anti-microbial properties of the cervical mucus plug [224][225][226][227][228][229] and predisposes to ascending intra-amniotic infection, or alternatively, if intra-amniotic infection leads to a short cervix.…”
Section: Discussionmentioning
confidence: 99%
“…While all pregnant women have microorganisms in the lower genital tract, most do not have intra-amniotic infection. The mucus plug represents an anatomical and functional barrier to ascending infection during pregnancy 69-75 . In the non-pregnant state, the endometrial cavity is not sterile 76-78 , but the decidua is thought to be sterile during pregnancy.…”
Section: Pathways Of Microbial Invasion Of the Amniotic Cavitymentioning
confidence: 99%
“…However, this hypothesis was refuted, and recent research has shown microorganisms detected even in the endometrial cavity of healthy asymptomatic women . Furthermore, the uterine mucus plug has been shown to incompletely block bacterial ascension by vaginal bacteria . Additionally, particles can translocate from the vagina to the uterus through the cervical canal within minutes by the function of the uterine peristaltic pump .…”
Section: Etiologymentioning
confidence: 99%
“…[22][23][24][25] Furthermore, the uterine mucus plug has been shown to incompletely block bacterial ascension by vaginal bacteria. 26,27 Additionally, particles can translocate from the vagina to the uterus through the cervical canal within minutes by the function of the uterine peristaltic pump. 27,28 Thus, the existence of microorganisms in the uterus has come to be accepted, and they are thought to be a main cause of CE, since antibiotic treatment has been reported to be an effective therapy for CE.…”
Section: Concept Of Cementioning
confidence: 99%